2016
DOI: 10.1016/j.ccell.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Profiles of Extra-cranial Malignant Rhabdoid Tumors Reveal Heterogeneity and Dysregulated Developmental Pathways

Abstract: Summary Malignant rhabdoid tumors (MRT) are rare, lethal tumors of childhood that most commonly occur in the kidney and brain. MRT are driven by SMARCB1 loss, but the molecular consequences of SMARCB1 loss in extra-cranial tumors have not been comprehensively described and genomic resources for analyses of extra-cranial MRT are limited. To provide such data, we used whole genome sequencing, whole genome bisulfite sequencing, whole transcriptome (RNA-Seq) and miRNA sequencing (miRNA-Seq), and histone modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
141
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(151 citation statements)
references
References 88 publications
8
141
1
1
Order By: Relevance
“…These findings have significant implications for ATRT treatment as the safety and efficacy of dasatinib are established in adults and children. Interestingly, consistent with the reported enrichment of BMP signaling/mesenchymal lineage genes in non-CNS RTs (Birks et al, 2011; Chun et al, 2016; Gadd et al, 2010), we observed an overlap in the methylation profiles of non-CNS RTs and group 2 ATRTs (data not shown), which suggests that some group 2 ATRTs and non-CNS tumors characteristically seen in very young children with rhabdoid predisposition syndrome, may have common or closely related cellular origins. Indeed, we observed that dasatinib and nilotinib also robustly inhibited the growth of G401, a renal RT cell line (data not shown) and suggest potential roles for dasatinib and nilotinib in non-CNS RT treatment.…”
Section: Discussionsupporting
confidence: 87%
“…These findings have significant implications for ATRT treatment as the safety and efficacy of dasatinib are established in adults and children. Interestingly, consistent with the reported enrichment of BMP signaling/mesenchymal lineage genes in non-CNS RTs (Birks et al, 2011; Chun et al, 2016; Gadd et al, 2010), we observed an overlap in the methylation profiles of non-CNS RTs and group 2 ATRTs (data not shown), which suggests that some group 2 ATRTs and non-CNS tumors characteristically seen in very young children with rhabdoid predisposition syndrome, may have common or closely related cellular origins. Indeed, we observed that dasatinib and nilotinib also robustly inhibited the growth of G401, a renal RT cell line (data not shown) and suggest potential roles for dasatinib and nilotinib in non-CNS RT treatment.…”
Section: Discussionsupporting
confidence: 87%
“…Aside from the loss of SMARCB1 in MRTs, prior studies that included SNP and exome analysis noted very little variation in MRT genomes[13, 2325]. Recent studies by Chun et al found clustering of CG island promoter methylation into two groups that correlated with age at diagnosis, which may provide a biological reason for the apparent survival benefit among older patients[26]. Similar to non-CNS rhabdoid tumors, recent investigations in transcriptomic and epigenetic organization of CNS AT/RTs suggests that these tumors can be subclassified into three distinct molecular subgroups with different preferred locations in the brain, suggesting they may originate from different precursor cells while maintaining their common loss of SMARCB1 [27].…”
Section: Discussionmentioning
confidence: 99%
“…The ongoing and detailed characterization of AT/RT and MRT (50,51) will likely lead to further biological insights that can better delineate molecular subtypes of these tumors and may lead to novel therapeutic avenues. Despite this progress, how best to approach early cancer surveillance for germline carriers at risk for these rare and aggressive tumors is likely to remain an area of significant clinical challenge.…”
Section: Discussionmentioning
confidence: 99%